2010
DOI: 10.1016/j.jacc.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Myocardial Fibrosis in Hypertrophic Cardiomyopathy

Abstract: In patients with HCM, myocardial fibrosis as measured by late gadolinium enhancement cardiovascular magnetic resonance is an independent predictor of adverse outcome. (The Prognostic Significance of Fibrosis Detection in Cardiomyopathy; NCT00930735).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
485
7
21

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 734 publications
(538 citation statements)
references
References 34 publications
20
485
7
21
Order By: Relevance
“…As in previous studies, 11,15 it remains to be proved whether LGE is an independent prognostic marker. Maron et al 12 reported a high prevalence, although not reaching statistical significance, of cardiovascular events during follow-up of 202 patients with HCM and LGE.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As in previous studies, 11,15 it remains to be proved whether LGE is an independent prognostic marker. Maron et al 12 reported a high prevalence, although not reaching statistical significance, of cardiovascular events during follow-up of 202 patients with HCM and LGE.…”
Section: Discussionmentioning
confidence: 83%
“…The mean age of our population (56.4±17.0 years) was older than in most studies in the literature 5,11,12 and included few patients in the age-group most associated with sudden death (<35 years). Most were asymptomatic or mildly symptomatic, as in other published series.…”
Section: Discussionmentioning
confidence: 83%
“…The DE is associated with the record of nonsustained ventricular tachycardia in Holter in multivariate analyses 75,78 , as well as the left ventricular reshaping and evolution of terminal dilated forms 74 . The association with the obstruction was not found in a study in which the prevalence of obstructive forms was similar between those with and without DE 76 . Longitudinal analyses showed relation between DE, sudden death and increased mortality, but it is still not proved [76][77][78] .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 74%
“…MRI with gadolinium detects and quantifies fibrosis areas with delayed enhancement (DE) of focal or diffuse character in 60-80% of patients with HCM, representing 0-40% of the LV myocardial mass [74][75][76][77][78] (Figure 4). The DE is associated with the record of nonsustained ventricular tachycardia in Holter in multivariate analyses 75,78 , as well as the left ventricular reshaping and evolution of terminal dilated forms 74 .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Assessment of late gadolinium enhancement (LGE) in the left or right ventricle was interpreted by blinded observers. When present, the amount of LGE was quantified in a 16-segment model based on the "full width at half maximum" technique by customized analysis software (MRI-MASS, Medis, Leiden, the Netherlands) [11]. …”
Section: Methodsmentioning
confidence: 99%